Pengujian CBR Laboratorium Mengggunakan Metode Tekanan (Pressure Method) untuk Tanah Timbunan Berdasarkan Energi Pemadatan - Sari, Dwi Winda; Adha, Idharmahadi; Zakaria, Ahmad (Universitas Lampung, 2019)
In building a construction related to the physical condition of the soil, this is because the land It is one of the very material plays an important role in supporting such a construction.Then had to do the testing power support basic land (subgrade) with experimental study testing the California Bearing Ratio (CBR) method of pressure (pressure method) based on the energy compaction. The research using a sample of the soil that came from the area of Tirtayasa, Kec.Sukabumi, Bandar Lampung for land fill. Implementation testing of CBR compactor modification press tool with using three soil samples at each pressure.The pressures used for CBR standard is 0,10 MPa, 0,26 MPa and 0.58 MPa. And for testing using pressure modified CBR 0.437 MPa,1,19 MPa and 2,63 MPa. The results of the research in the laboratory showed that the weight of the maximum volume (γdmaks) of 1.68 g/cm3 of standard proctor method.While of modified proctor testing the the weight of the maximum volume (γdmaks) of 1.77 gr/cm3. Based on the results of testing the value of CBR standard and modified methods of compared that the laboratory testing higher than the CBR based on compaction energy with press modifications. Keywords : CBR, Compaction Energy Tool press the Compactor Modification